Perancangan Sistem E-Commerce Berbasis Web dengan Metode System Development Life Cycle untuk Usaha Mikro Kecil dan Menengah Pakaian di Kota Batam - Yefta Christian; Tony Wibowo; Putra Agung Winata (KLIK: Kajian Ilmiah Informatika dan Komputer, 2023)
E-commerce is one of the major innovations in the business world in this era of globalization, so this innovation must continue to be developed so that it can help a business in business efficiency. This design aims to design a Web-Based E-Commerce System using the System Development Life Cycle (SDLC) Method to support Micro, Small and Medium Enterprises (MSMEs) in the clothing industry in Batam City. The method that will be used is to identify target users through qualitative methods, including interviews and needs analysis, to understand the characteristics, preferences and challenges faced by stakeholders in the e-commerce context and using the System Development Life Cycle (SDLC) method in design. web-based e-commerce. Designing an e-commerce system that suits the needs and preferences of target users. So based on this design evaluation, the results can be the answer to the problems faced and help efficiency in a business.